INNOVATIVE TECHNOLOGIES IN THE INSURANCE SECTOR (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article presents key financial technologies, main financial products and services using Fintech and InsurTech technologies that influence the development and functioning of financial sectors such as insurance activities. The factors stimulating their development and the main changes in this area are identified. Considerable space is devoted to the prospects for their application, as well as an analysis of the problems that need to be solved in order to remove obstacles to their wider distribution by Fintech and InsurTech technologies.